Analysis of the effective production Kanban size with triggering system for achieving just-in-time (JIT) production - Ani, C. (Institute of Electrical and Electronics Engineers Inc., 2018)
In this paper, the improvement activity in manufacturing plant has been conducted by focusing on the effective Kanban size to achieve just-in-time (JIT) production system. The results of the implementation in case study was identified, analyzed and verified by utilizing the effective feeders of Kanban size through queuing system analysis. The ultimate objective was to ensure adaptation of the developed Kanban approach using effective feeders for in-house production system was implemented, in which work-in-progress (wip) 'triggering system' was introduced to ensure sustainability of the Kanban system and to achieve the JIT production system. Based on the implementation from the case study industry, the obtained result for effective feeders of Kanban size was dual feeders and with the waste of waiting eliminated by 36.64. Through effective production Kanban size, the waiting time of the production process in production losses time due to the pre-preparation part had been identified and successfully minimized. Â© 2018 IEEE.